Enhancing Public Service Quality Through the Lens of Islamic Economics - Nurhayati, Endang; Mustafidah, Wiwit (Islamic Micro Finance Journal, 2025)
This study aims to evaluate the quality of public services from an Islamic economic perspective. A qualitative method was employed, with data collected through observation, interviews, and documentation techniques. The study was conducted in Dasri Village, Tegalsari Subdistrict, Banyuwangi District, East Java, Indonesia. The findings highlight several key indicators of public service quality in governance based on an Islamic perspective: fairness, transparency and accountability, community welfare, and community participation in decision-making. Fairness is implemented by the government through the principle of Amanah, emphasizing sincerity and a free-of-charge service system. Transparency and accountability are demonstrated through an open system without concealed information, allowing the public to access all relevant processes. Community participation in decision-making is facilitated through regular meetings and discussion forums, enabling the government to incorporate community input and actively involve citizens. Lastly, community welfare is promoted by ensuring effective access to services and fostering strong relationships between the village government and its residents